A study on the information-seeking behavior of students in selected high schools in Novaliches, Quezon City regarding adolescent sexuality - Adolfo, Jill Anne L.; Gonzales, Grace Marie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
Adolescence is a crucial stage in one's life wherein many life-changing events occur. It is also the stage where naturally occurring phenomenon such as sexual impulses and socializing agents such as one's environment influence the decision making and actions of the individual. This study attempted to describe the information-seeking behavior of selected third year and fourth year high school students in public and private schools in Novaliches, Quezon City.
Four hundred thirty five (435) respondents from Novaliches High School, Dona Rosario High School, Springfield School of Novaliches and St. John of Beverley School were asked to participate in answering survey questionnaires which were designed to determine their thoughts, actions, and feelings about sexuality. Interviews from various school librarians, teachers and school authorities were also included.
Using the measures of central tendencies and frequency in arranging the collected data, the study was able to show that the respondents who were mostly 15-16 year olds can be described as "independent seekers" for they prefer their source of information regarding sexuality to come from the Internet. The Internet was also one of the sources of information within the respondents reach, together with books and magazines. Although, most of the respondents expressed positive feelings with their information seeking about sexuality, there is still a need for mediators such as their parents, teachers, librarians and school administrators to address their needs by being active and having an objective approach in their information dissemination.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information behavior -- Philippines -- Novaliches (Quezon City).; High school students -- Philippines -- Novaliches (Quezon City).; Public schools -- Philippines -- Novaliches (Quezon City).; Private schools -- Philippines -- Novaliches (Quezon City).; Teenagers -- Sexual behavior -- Philippines -- Novaliches (Quezon City).